International origins of national unsustainability: market, dependency and policies - Moniruzzaman, Md. (2019)
Sustainable development has become a global economic objective at all levels- local, national and international. The concept has gained popular global currency due to the adverse effects of global warming, risks of global economic interdependency and competitiveness of national economies. However, it applies more on the developing and poor economies that aspire to become developed economies. The pressure of global forces often make those economies face unavoidable situations that lead to heavy compromise with development achievements, thereby making sustainable development impossible. This article argues that development initiatives of the poor and developing countries persistently face the risk of unsustainability due to the changes in international market behavior; local dependency on foreign exchange regime, changes in global climate patterns; and local policy changes leading to inflation, and real income decline. All these cause the economy backslide periodically making development unsustainable. Data for this study come from twenty poor and developing economies of Asia, Africa and Latin American continents over the past fifty years. A time series analysis of the data would conclude that sustainability of national development in the poor and developing economies is heavily compromised by international factors.